How we implemented a resident-led medical simulation curriculum in a large internal medicine residency program. (April 2014) - Mathai, Susan K.; Miloslavsky, Eli M.; Contreras-Valdes, Fernando M.; Milosh-Zinkus, Tanya; Hayden, Emily M.; Gordon, James A.; Currier, Paul F.
Abstract Mannequin-based simulation in graduate medical education has gained widespread acceptance. Its use in non-procedural training within internal medicine (IM) remains scant, possibly due to the logistical barriers to implementation of simulation curricula in large residency programs. We report the Massachusetts General Hospital Department of Medicine's scale-up of a voluntary pilot program to a mandatory longitudinal simulation curriculum in a large IM residency program (n = 54). We utilized an eight-case curriculum implemented over the first four months of the academic year. An intensive care unit curriculum was piloted in the spring. In order to administer a comprehensive curriculum in a large residency program where faculty resources are limited, thirty second-year and third-year residents served as session facilitators and two senior residents served as chairpersons of the program. Post-session anonymous survey revealed high learner satisfaction scores for the mandatory program, similar to those of the voluntary pilot program. Most interns believed the sessions should continue to be mandatory. Utilizing residents as volunteer facilitators and program leaders allowed the implementation of a well-received mandatory simulation program in a large IM residency program and facilitated program sustainability.